Machine learning to predict radiomics models of classical trigeminal neuralgia response to percutaneous balloon compression treatment - Ji Wu; Chengjian Qin; Yixuan Zhou; Xuanlei Wei; Deling Qin; Keyu Chen; Yuankun Cai; Lei Shen; Jingyi Yang; Dongyuan Xu; Songshan Chai; Nanxiang Xiong (Frontiers in Neurology)
BackgroundClassic trigeminal neuralgia (CTN) seriously affects patients’ quality of life. Percutaneous balloon compression (PBC) is a surgical program for treating trigeminal neuralgia. But some patients are ineffective or relapse after treatment. The aim is to use machine learning to construct clinical imaging models to predict relapse after treatment (PBC).MethodsThe clinical data and intraoperative balloon imaging data of CTN from January 2017 to August 2023 were retrospectively analyzed. The relationship between least absolute shrinkage and selection operator and random forest prediction of PBC postoperative recurrence, ROC curve and decision -decision curve analysis is used to evaluate the impact of imaging histology on TN recurrence.ResultsImaging features, like original_shape_Maximum2D, DiameterRow, Original_Shape_Elongation, etc. predict the prognosis of TN on PBC. The areas under roc curve were 0.812 and 0.874, respectively. The area under the ROC curve of the final model is 0.872. DCA and calibration curves show that nomogram has a promising future in clinical application.ConclusionThe combination of machine learning and clinical imaging and clinical information has the good potential of predicting PBC in CTN treatment. The efficacy of CTN is suitable for clinical applications of CTN patients after PBC.